2017
DOI: 10.1016/s1470-2045(17)30252-8
|View full text |Cite
|
Sign up to set email alerts
|

The future of personalised radiotherapy for head and neck cancer

Abstract: Radiotherapy has long been the mainstay of treatment for patients with head and neck cancer and has traditionally involved a stage-dependent strategy whereby all patients with the same TNM stage receive the same therapy. We believe there is a substantial opportunity to improve radiotherapy delivery beyond just technological and anatomical precision. In this Series paper, we explore several new ideas that could improve understanding of the phenotypic and genotypic differences that exist between patients and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(124 citation statements)
references
References 60 publications
1
122
0
1
Order By: Relevance
“…24 We note the emerging role of precise and personalized oncology, which could greatly improve the clinical outcomes of therapies, integrating the biological differences between tumor phenotypes, based on a large dataset of genomics and radiomics biomarkers. 40,41 In this regard, functional MRI techniques, such as diffusion-as well as perfusion-MRI, could have an important role, as they can provide several quantitative indices strictly related to tissue cellular density, vascular perfusion, and tumor heterogeneity. 42 These indices represent distinctive tumor signatures with radiobiological relevance that could guide treatment optimization and personalization.…”
Section: Discussionmentioning
confidence: 99%
“…24 We note the emerging role of precise and personalized oncology, which could greatly improve the clinical outcomes of therapies, integrating the biological differences between tumor phenotypes, based on a large dataset of genomics and radiomics biomarkers. 40,41 In this regard, functional MRI techniques, such as diffusion-as well as perfusion-MRI, could have an important role, as they can provide several quantitative indices strictly related to tissue cellular density, vascular perfusion, and tumor heterogeneity. 42 These indices represent distinctive tumor signatures with radiobiological relevance that could guide treatment optimization and personalization.…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck cancer, such as oropharyngeal head and neck squamous cell carcinoma and non‐oropharyngeal head and neck squamous cell carcinoma, different cell sublines have different radiosensitivity factors and different resistance to radiation. Radiomics can also identify sublines (subregions) of radioresistant cells in the tumor, so that individual therapeutic protocols can be developed to selectively increase the dose of radiation to these sublines of cells 19 . In a 2014 study, Aerts et al.…”
Section: Application Of Radiomics In Radiotherapymentioning
confidence: 99%
“…Radiomics can also identify sublines (subregions) of radioresistant cells in the tumor, so that individual therapeutic protocols can be developed to selectively increase the dose of radiation to these sublines of cells. 19 In a 2014 study, Aerts et al showed that a radiomic signature composed of four features models can provide prognostic information about intratumoral heterogeneity and can be used to predict survival, pathological grading, and gene expression typing. 20 In addition to these studies, in head and neck cancer radiotherapy, the parotid gland usually receives a higher dose of radiation.…”
Section: Radiomics In Head and Neck Cancermentioning
confidence: 99%
“…Greater than two-thirds of all patients with HNSCC will receive IR at some point during their treatment (6) . Significant pre-clinical data suggests that IR is additive or synergistic with different forms of immunotherapy, including checkpoint inhibition.…”
Section: Introductionmentioning
confidence: 99%